2001
DOI: 10.1121/1.1360717
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between spectral characteristics and perceived hypernasality in children

Abstract: The purpose of this study was to quantify perceived hypernasality in children. One-third octave spectra of the isolated vowel [i] were obtained from 32 children with cleft palate and 5 children without cleft palate. Four experienced listeners rated the severity of hypernasality of the 37 speech samples using a 6-point equal-appearing interval scale. When the average 1/3-octave spectra from the hypernasal group and the normal resonance group were compared, spectral characteristics of hypernasality were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 13 publications
2
35
0
6
Order By: Relevance
“…[36][37][38]41,42 In this study, we analyzed a number of synthetic nasal vowels and identified various acoustic characteristics of nasalization that were consistent with prior findings. As demonstrated by the examples in Fig.…”
Section: A Articulatory and Acoustic Characteristics Of Nasal Vowelssupporting
confidence: 65%
See 2 more Smart Citations
“…[36][37][38]41,42 In this study, we analyzed a number of synthetic nasal vowels and identified various acoustic characteristics of nasalization that were consistent with prior findings. As demonstrated by the examples in Fig.…”
Section: A Articulatory and Acoustic Characteristics Of Nasal Vowelssupporting
confidence: 65%
“…The articulatory adjustment was derived using the simulated annealing algorithm by coordinating the articulatory parameters (i.e., ART) of the speaker-adaptive model when the velopharyngeal port remained open to match the acoustic features (i.e., F1, F2, F3) calculated from the transfer function of model with that of a target oral vowel with a closed velopharyngeal port. Although the acoustic cues of nasalization are much beyond the three lowest formant frequencies, [36][37][38] incorporating these additional acoustic cues into the articulatory adjustment process largely increased the computation time. Due to the exploratory nature of this study, we only considered the three lowest formant frequencies, which can be computed in an efficient manner based on the transfer functions.…”
Section: Oropharyngeal Articulatory Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency instability, high intensity, abnormal formant distribution and abnormal spectrograms have been reported [10][11][12]. In 1989, Zajac and Linvile [11] studied voice perturbations in patients with VPI.…”
Section: Introductionmentioning
confidence: 99%
“…They were instructed to indicate the degree of perceived nasality in the speech samples based on the 6-point scale, where grade 0 representing "no nasal resonance" and 1, 2, 3, 4 and 5 representing "mild," "mild-moderate," "moderate," "moderately severe," and "severe hypernasal resonance" respectively. Earlier studies used similar scale to rate hypernasality [6,12]. They were further instructed not to pay attention to any other parameter of speech (voice, articulation, prosody etc) while they were doing the rating.…”
Section: Perceptual Analysismentioning
confidence: 99%